Factors Affecting Millennial Employee Engagement in DKI Jakarta - Fika Kristiyadi; Oetami P. Winarto (CV. Syntax Corporation Indonesia, 2025)
This study aims to analyze the influence of self-efficacy, perceived organizational support, and work environment on employee engagement among millennial employees in DKI Jakarta, with work-life balance serving as both an intervening and moderating variable. The phenomenon of low employee engagement among millennials has become a major concern, as this generation is characterized by unique traits such as a preference for flexibility, work-life balance, and high expectations of organizational support. To address this issue, the study investigates how internal factors like self-efficacy, as well as external factors such as organizational support and the work environment, can enhance employee engagement through the mediating role of work-life balance. The research employs a quantitative method using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach with SmartPLS 4.0 software. Data were collected from 120 millennial respondents working in various industrial sectors in DKI Jakarta through an online questionnaire. The analysis involved validity and reliability tests, structural model evaluation, and hypothesis testing. The results reveal that self-efficacy and perceived organizational support have a positive and significant effect on employee engagement, whereas work environment does not show a significant impact. Furthermore, work-life balance acts as both a mediator and moderator, strengthening the relationship between perceived organizational support, work environment, and employee engagement. These findings highlight the importance of fostering an organizational culture that not only promotes employee involvement but also supports a healthy work-life balance, while simultaneously developing self-efficacy to improve millennial engagement in the workplace